The Effect of Learning Style on Academic Achievement of Prospective Teachers in Mathematics Education - Kurniawan, Agus Prasetyo; Hartono, Sugi (Universitas Negeri Surabaya, 2020)
This study aims to determine the effect of learning styles on academic achievement of prospective teachers in mathematics education. The method used in this research is descriptive analytic with cross sectional approach. The subjects in this study were 66 students of 5th semester mathematics education teacher candidates at the State Islamic University of Sunan Ampel Surabaya, Indonesia. Data were collected by two methods, namely the questionnaire method or questionnaire through the Visual Auditory and Kinesthetic (VAK) test to collect student learning style data and the documentation method to collect student academic achievement data which was carried out by using the chi square test to see the relationship between learning styles and academic achievement. The results showed that the most student learning styles were visual learning styles (54.5%), then auditory learning styles (24.2%) and finally kinesthetic learning styles (13.6%). Furthermore, there were some students who chose more than one learning style, namely visual-auditory (3.1%), visual-kinesthetic (3.1%), and auditory-kinesthetic (1.5%). After performing the statistical test, namely the chi square test, it is obtained that X2 count = 4.497 is greater than X2 table = 3.9403 at a significant level of 0.05. This shows that there is a relationship between learning styles and academic achievement of prospective mathematics education teacher students. Keywords: learning style, academic achievement, prospective teachers, mathematics education